The role of endobronchial ultrasound-guided transbronchial needle aspiration in stereotactic body radiation therapy for non-small cell lung cancer. (September 2018) - Hashimoto, Kohei; Daddi, Niccolò; Giuliani, Meredith; Hope, Andrew; Le, Lisa W.; Czarnecka, Kasia; Cypel, Marcelo; Pierre, Andrew; de Perrot, Marc; Darling, Gail; Waddell, Thomas K.; Keshavjee, Shaf; et al.
Highlights: We assessed the diagnostic power of EBUS-TBNA for nodal status in SBRT candidates. PET had a significant rate of false positive nodes in SBRT candidate in our cohort. Ones with image positive and EBUS negative node were matched with image negative. The oncological outcomes after SBRT were comparable between matched groups. SBRT candidates with image positive lymph node can be considered for EBUS-TBNA. Abstract: Objective: To evaluate the diagnostic value of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in stereotactic body radiation therapy (SBRT) candidates and compare with computed tomography (CT) and positron emission tomography (PET). Methods: Inclusion criteria for this single institutional retrospective study were 1) biopsy-proven or suspicious NSCLC with diameter <6 cm; 2) no distant metastasis; 3) EBUS-TBNA staging between April 2008 and November 2014; 4) SBRT eligible. CT and PET positive nodes were defined as short axis ≧1 cm and standardized uptake value ≧2.5, respectively. Node positive by clinical-pathologic confirmation (NPCP) was defined as confirmed malignancy by EBUS-TBNA or recurrence in hilar or mediastinal lymph nodes within one year after SBRT. The survival after SBRT was compared between radiologically node-positive, but EBUS-TBNA negative, patients (Case) and a matched cohort (tumor size; radiation dose; operability) who underwent SBRT without EBUS-TBNA staging (Control). Results: There were 35 eligible patients (mean age 77 ± 8.2; mean diameter 2.5 ± 1.0 cm). Thirty were medically inoperable. Twenty out of 24 patients with radiologically positive node(s) were negative by EBUS-TBNA. All eleven radiologically negative patients were N0 following EBUS-TBNA. Thirty-one patients underwent SBRT. Per-person based sensitivity/specificity of CT, PET and EBUS-TBNA for NPCP were 42.9/64.3%, 100/64.3% and 57.1/100%, respectively. A 1:4 match was obtained. Regional failure-free survival (p = 0.71; HR = 0.88 95%CI 0.45–1.74) and disease-free survival (p = 0.77; HR = 1.10 95%CI 0.58–2.11) of the Case were not significantly different from the Control. Conclusion: Patients with radiographically positive lymph nodes can be considered for EBUS-TBNA and may remain candidates for SBRT.